MEDIA FRAMING OF TECHNOLOGICAL ADVANCEMENT AND HUMAN RIGHTS TO SAUDI ARABIA'S NEOM PROJECT - Dianatul Ilmi; Moh Zawawi (UIN Raden Mas Said Surakarta, 2024)
This research examines how Asharq al-Awsat and ALQST media framed the NEOM infrastructure project in Saudi Arabia. NEOM is a futuristic city project that is part of Saudi Arabia's Vision 2030. The project is designed to be the center of technological innovation, environmental sustainability, and economic development in the northwestern region of Saudi Arabia. It also explores the framing tools used and their impact on public perception and global outlook. This research uses a qualitative approach with Gamson and Modigliani’s framing analysis. The results show that Asharq al-Awsat tends to frames the NEOM project as a form of technological progress and innovation that provides economic benefits. Meanwhile, ALQST highlights the negative impacts such as human rights violations and environmental damage. These framing differences affected public perception and political discourse regarding the project. This research expands the understanding of how the media frames large infrastructure projects in the Middle East region. In addition, it reveals the implications of framing for public perception and international policy regarding infrastructure projects and human rights.